2019
DOI: 10.3390/brainsci9110308
|View full text |Cite
|
Sign up to set email alerts
|

The Practical Use of White Cell Inflammatory Biomarkers in Prediction of Postoperative Delirium after Cardiac Surgery

Abstract: Introduction: Postoperative delirium (POD) is associated with unfavorable outcomes. It may result from neuroinflammation and oxidative stress. The aim of this study was to evaluate the role of routinely available inflammatory markers derived from white blood cell count (WBC), for prognostic value in diagnosing delirium after cardiac surgery. Methods: We performed an analysis of data collected from patients undergoing planned coronary artery bypass grafting (CABG). Differential WBC and CRP (C-reactive protein) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 40 publications
2
66
0
1
Order By: Relevance
“…An accurate prediction of outcome after an emergency surgery would better assist clinicians when discussing mortality with the patients and their families and guiding difficult treatment decisions [5]. The physiological immune response of circulating leucocytes to various stressful events is often characterized by an increase in neutrophil count and a decline in lymphocyte count along with a decrease in platelet count [6]. The NLR and PLR are simple, readily available laboratory variables.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate prediction of outcome after an emergency surgery would better assist clinicians when discussing mortality with the patients and their families and guiding difficult treatment decisions [5]. The physiological immune response of circulating leucocytes to various stressful events is often characterized by an increase in neutrophil count and a decline in lymphocyte count along with a decrease in platelet count [6]. The NLR and PLR are simple, readily available laboratory variables.…”
Section: Discussionmentioning
confidence: 99%
“…The search for an ideal delirium marker is a complex process as many confounding factors account for delirious state postoperatively [ 61 ]. It is much more probable that this will be based on the identification of a panel of biomarkers in order to make an accurate and quick diagnosis [ 51 , 62 ].…”
Section: Biomarkers In Delirium Diagnosismentioning
confidence: 99%
“…This is consistent with the data reported by Çinar et al that CRP, although elevated, cannot be considered as an independent risk factor in the development of POD [ 98 ]. On the other hand, a study, including the CRP levels performed by Kotfis et al, showed a correlation between increased CRP levels and delirium [ 62 ].…”
Section: Inflammation-related Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations